Experimental validation of variable temperature flow field concept for proton exchange membrane fuel cells. (12th October 2017) - Penga, Željko; Pivac, Ivan; Barbir, Frano
Abstract: Variable temperature flow field concept allows maintaining close to 100% relative humidity along the entire flow field of the anode and the cathode side without external humidification using water generated during fuel cell operation for internal reactant humidification. This work deals with the experimental validation of the variable temperature flow field concept on a five-segment single cell. The experimental setup provides insight into the membrane water transport, temperature distribution on the current collectors and inside the channels, and the current density distribution along the cell. Variable temperature flow field operation with dry reactants is compared to isothermal operation with partially and fully humidified reactants. The polarization curve comparison shows that the variable temperature flow field operating efficiency is similar or better than the commonly used isothermal configuration with fully humidified reactants. The main contribution of the variable temperature flow field concept, when compared to isothermal operation, is the reduction of the mass transport losses at higher currents, since the generated water is evaporated in the stream of reactants, thereby minimizing the problem of liquid water removal from the cell. Highlights: Segmented fuel cell allowing variable temperature along the channel is constructed. Temperature and relative humidity along the channel may be tracked in h-x diagram. Variable temperature along the channel allows operation with dry reactant gases.